The Role of Well-Being, Divergent Thinking, and Cognitive Reserve in Different Socio-Cultural Contexts - Francesca Garau; Alessandro Antonietti; Natale Salvatore Bonfiglio; Beatrice Madeddu; Maura Crepaldi; Jessica Giannì; Giulia Fusi; Laura Colautti; Virginia Maria Borsa; Massimiliano Palmiero; Maria Luisa Rusconi; Maria Pietronilla Penna (Brain Sciences)
Background: Many protective factors promote psychological well-being (PWB) in the elderly and contribute to healthy aging, such as engagement, positive emotions, and cognitive reserve (CR), which includes education, leisure, and work activities. CR sustains cognitive functioning and positively correlates with creativity, particularly divergent thinking (DT), helping older adults cope with everyday challenges and enhancing their PWB. Objectives: The present study aimed to investigate the relationships between DT, CR, PWB, memory functions, depression, stress, and anxiety indexes even in the Blue Zone (BZ), an area known for extraordinary longevity and high PWB. Methods: A total of 165 Italian healthy older adults (Mage = 73.8, SD = 6.7) from Milan (MI), Bergamo (BG), Cagliari (CA), and BZ were enrolled and divided into four groups according to their origin. Generalized linear models (GLMs) with normal and gamma link functions were used. Results: BZ presented higher DT and PWB indices than the cities but lower CR, particularly in education. Conclusions: This study highlights the influence of DT in supporting cognitive functions and PWB, suggesting that PWB and DT are key protective factors in aging.